2010
DOI: 10.1042/bst0381615
|View full text |Cite
|
Sign up to set email alerts
|

Cutting the nonsense: the degradation of PTC-containing mRNAs

Abstract: In eukaryotes, mRNAs harbouring PTCs (premature translation-termination codons) are recognized and eliminated by NMD (nonsense-mediated mRNA decay). In addition to its quality-control function, NMD constitutes a translation-dependent post-transcriptional pathway to regulate the expression levels of physiological mRNAs. In contrast with PTC recognition, little is known about the mechanisms that trigger the rapid degradation of mammalian nonsense mRNA. Studies have shown that mammalian NMD targets can be degrade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
85
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(87 citation statements)
references
References 61 publications
1
85
0
Order By: Relevance
“…Previously, mRNA 3= tagging has been linked to mRNA degradation, being coincident with decapping and the initiation of transcript degradation (60,76). NMD is a well-conserved degradation process, which rapidly eliminates transcripts containing a PTC, thus preventing accumulation of truncated proteins (69). Previously, we have shown that uaZ14, a mutant allele of the urate oxidaseencoding gene, is subject to NMD and that this is dependent on the fidelity of NmdA/Upf2 (63).…”
Section: Resultsmentioning
confidence: 99%
“…Previously, mRNA 3= tagging has been linked to mRNA degradation, being coincident with decapping and the initiation of transcript degradation (60,76). NMD is a well-conserved degradation process, which rapidly eliminates transcripts containing a PTC, thus preventing accumulation of truncated proteins (69). Previously, we have shown that uaZ14, a mutant allele of the urate oxidaseencoding gene, is subject to NMD and that this is dependent on the fidelity of NmdA/Upf2 (63).…”
Section: Resultsmentioning
confidence: 99%
“…6), which could be explained by nonsense-mediated mRNA decay of the tva r3 transcript with retained intron 1 (reviewed in reference 27). This kind of mRNA decay generally requires that translation terminate sufficiently upstream of an exon-exon junction (29,30), and the premature stop codon in the longer transcript positioned 76 nucleotides upstream of the exon 4-exon 5 junction can be a proper target. Sometimes, in retroviral full-length transcripts, the stop codon can be masked by highly structured stability elements (42).…”
Section: Discussionmentioning
confidence: 99%
“…First, AS can regulate transcript levels by the introduction of premature termination codons (PTCs), which commit the transcript isoform to degradation by the nonsense-mediated decay (NMD) pathway. Linked AS-NMD thus regulates the level of functional mRNA transcripts (which encode protein) via targeted degradation of alternative splice forms (McGlincy and Smith, 2008;Nicholson and Mühlemann, 2010), and in Arabidopsis thaliana, at least 13% of genes undergo AS-NMD . The second main consequence of AS is where transcript isoforms give rise to proteins that differ in their sequence and domain arrangement and thus may widely differ in subcellular localization, stability, or function (Syed et al, 2012).…”
Section: Introductionmentioning
confidence: 99%